Poly-Electrolyte Complex: A Novel System for Biomedical Applications and Recent Patents - Deeksha; Malviya, Rishabha; Kr. Sharma, Pramod (Recent Patents on Nanotechnology, 2014)
Polyelectrolyte complexes are getting more attention owing to their formation by the interaction of opposite charges with the help of electrostatic force. Polyelectrolyte complexation reduces the toxic effects of the cross-linking agents. Polyelectrolyte complexescan be classified on various bases. The current report highlights properties, factors affecting it and various technologies. In the present report we intend to discuss the applications of polyelectrolyte complexes such as biomedical, controlled delivery, medicine, and area which can cause controlled release in different aspects. Patents related to these inventions are added along with their pivotal roles.
Keywords: drug delivery